2013
DOI: 10.11133/j.tpr.2013.63.3.005
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Relational Assessment Procedure and Body-Weight Bias: Influence of Gender of Participants and Targets

Abstract: The Implicit Relational Assessment Procedure (IRAP) and explicit measures were used with 21 college students to determine if body weight of target stimuli (photographic images of slim and overweight individuals) influenced perceptions of intelligence. The explicit measure was a computerized adaptation of the Anti-Fat Attitudes Questionnaire designed to reduce participant error. A Covert Perception Task was developed as an additional explicit measure in which participants rated the likelihood of success of slim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…This general tendency is stronger for women highly dissatisfied with their bodies. This pattern of results indicating stronger explicit than implicit weight bias is similar to that found in Maroto-Expósito et al (2015), but uncommon in the literature on body-size attitudes, where stronger bias is usually found for implicit than for explicit attitudes (Teachman et al, 2003; Roddy et al, 2010, 2011; Nolan et al, 2013). In our view, this discrepancy in the findings may be related to the fact that only the Maroto-Expósito et al study and this one have employed as an explicit measure a VAS for the same target images presented in the IRAP.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This general tendency is stronger for women highly dissatisfied with their bodies. This pattern of results indicating stronger explicit than implicit weight bias is similar to that found in Maroto-Expósito et al (2015), but uncommon in the literature on body-size attitudes, where stronger bias is usually found for implicit than for explicit attitudes (Teachman et al, 2003; Roddy et al, 2010, 2011; Nolan et al, 2013). In our view, this discrepancy in the findings may be related to the fact that only the Maroto-Expósito et al study and this one have employed as an explicit measure a VAS for the same target images presented in the IRAP.…”
Section: Discussionsupporting
confidence: 89%
“…These findings reveal that self-reported levels of BD are clearly associated with implicit body-image attitudes toward other females’ body shape as measured by the IRAP. Given that previous studies (Roddy et al, 2010, 2011; Nolan et al, 2013) on the topic did not collect information on participants’ levels of BD, it is difficult to elucidate whether inconsistent findings across studies (cf. Roddy et al, 2010; Maroto-Expósito et al, 2015) are attributable to differences in BD across samples from different cultural contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Roddy et al (2011Roddy et al ( , 2012; see also Nolan, Murphy, & Barnes-Holmes 2013) reported that what was driving the pro-thin/anti-fat bias in the IAT was an extremely strong pro-thin bias with participants having a neutral implicit attitude towards fat people.…”
Section: Flaws In the Irapmentioning
confidence: 99%
“…Stimuli for the nature IRAP were chosen from past implicit research (e.g., Greenwald et al, 1998). The 12 images for the weight IRAP were taken from Nolan et al (2013) and consisted of three pictures of women and three pictures of men, before and after they had lost a significant amount of weight. These images were controlled on a number of dimensions (e.g., picture angle, cropping, clothing and background).…”
Section: Apparatus and Materialsmentioning
confidence: 99%